Echocardiographic characteristics of patients with ischemic and non-ischemic chronic heart failure with reduced ejection fraction - N. N. Ilov; D. R. Stompel; S. A. Boytsov; E. I. Romantsov; A. A. Nechepurenko (Кардиоваскулярная терапия и профилактика)
TThe data indicate differences in the adverse outcomes of chronic heart failure (CHF) in both ischemic (ICMP) and non-ischemic origins. The knowledge of the structural and functional myocardial state, especially of the left ventricle (LV), is insufficient for accurate risk stratification of unfavorable events in different etiopathogenetic forms of CHF.Aim. To make a comparative analysis of echocardiographic characteristics of CHF patients with reduced LV ejection fraction (EF) ≤35% depending on the origin of CHF.Material and methods. 498 patients of CHF 3-4 functional class of NYHA (New-York Heart Association) with EF ≤35% taking optimal drug therapy were included in the study. Based on the etiology of CHF, two groups of patients with CHF of ischemic genesis (n=254) and dilated cardiomyopathy (DCMP, n=244) were formed. Two-dimensional echocardiography techniques in Band M-mode, color Doppler, and tissue Doppler imaging were carried out.Results. Patients with ICMP and DCMP had the same pattern of LV remodeling (mainly on the type of eccentric hypertrophy), but they reliably differed in the basic parameters of LV architectonics: endsystolic and end-diastolic dimensions, LV volume, LV myocardial mass and values of these indicators, indexed by body surface area. DCMP patients had a higher value of medial-lateral dimension and volume of left atrial, pathological mitral and tricuspid regurgitation was registered more often.Conclusion. It was found that left heart dimensions and volumes of DCMP patients exceed similar parameters in patients with ICMP. The possible association of the results with future adverse outcomes of CHF demands further research.